Service Delivery System and Satisfaction in influencing Customer Loyalty at Balung Regional Hospital - Robustin, Tri Palupi; Putri, Nur Latifa Isnaini; Hakim, Ihkwanul (Jurnal Ilmu Manajemen Advantage, 2024)
Due to the fact that as different consumers' needs change, one of those needs is the need for an abstract service, which is currently the largest sector supporting the Indonesian economy. Service providers must be able to satisfy customers to build client loyalty with an appropriate service plan. Service encounter and servicecape represent the service plan. This research aims to determine the effect of customer experience, satisfaction, and servicescape on customer loyalty. This study uses a survey research design, which is a quantitative research methodology, and the population is patients of Balung Hospital. By using a sample of 80 people, the sampling method used is accidental sampling. the data test stages in this study include validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, partial hypothesis testing and determination test. Multiple linear regression analysis is the method used in this study for data analysis. The research findings show that customer experience affects loyalty, loyalty is positively and significantly influenced by satisfaction variables, loyalty is significantly and favorably influenced by servicescape variables.